2022
DOI: 10.1093/eurpub/ckac129.475
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Healthcare Service Access among Persons with Spinal Cord Injury (SCI)

Abstract: Background Despite having a high healthcare need, persons with complex conditions are less likely to receive comprehensive care. Individuals with SCI experience difficulties accessing services 2-4 times more than the general population. There is little agreement concerning the factors that influence these access restrictions. Few studies focus on health system impact on characteristics on access. Objective To outline barriers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…20 A recent study on needs after spinal cord injury reported that younger persons had higher odds of unmet needs. 7 Additionally, older persons with disability might be less likely to report unmet needs having lower expectations and higher patient satisfaction. 21 Furthermore, preinjury comorbidities also increase the probability of unmet rehabilitation needs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 A recent study on needs after spinal cord injury reported that younger persons had higher odds of unmet needs. 7 Additionally, older persons with disability might be less likely to report unmet needs having lower expectations and higher patient satisfaction. 21 Furthermore, preinjury comorbidities also increase the probability of unmet rehabilitation needs.…”
Section: Discussionmentioning
confidence: 99%
“…This finding could be related to a lower ability to adapt to stressful events and greater support needs in younger patients in the trauma population 20 . A recent study on needs after spinal cord injury reported that younger persons had higher odds of unmet needs 7 . Additionally, older persons with disability might be less likely to report unmet needs having lower expectations and higher patient satisfaction 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation